2016
DOI: 10.13188/2380-6842.1000013
|View full text |Cite
|
Sign up to set email alerts
|

Provisional Study of Kuwait Adult Hematology Reference Range

Abstract: Introduction: Hematology reference range provides valuable information for the correct interpretation of results for proper diagnosis and treatment. Previous studies have shown that hematology reference range may vary in people of various continents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In the current study, the lower limit of Hb in the female group was lower compared with the Caucasians (France and Canada) (1,35) and also the populations in Oman and Kuwait (3,14). A possible explanation of the Hb difference compared to Caucasians is the prolonged menstrual cycle in Saudi women [median bleeding days were 5 (1-16)] (36).…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…In the current study, the lower limit of Hb in the female group was lower compared with the Caucasians (France and Canada) (1,35) and also the populations in Oman and Kuwait (3,14). A possible explanation of the Hb difference compared to Caucasians is the prolonged menstrual cycle in Saudi women [median bleeding days were 5 (1-16)] (36).…”
Section: Discussionmentioning
confidence: 46%
“…The reported hematological parameters RIs in literature differ for populations, for example, Asian Americans and American blacks compared to white Americans ( 4 ), South Indians compared to European ( 5 ) and Africans compared to Western populations ( 30 , 31 ). Few studies recently reported hematological RIs in the Middle Eastern region ( 3 , 7 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations